Initial coin offerings: An emergent research area - Brochado, A.; Troilo, M. L. (Digital Policy, Regulation and Governance, 2021)
Purpose – The purpose of this paper is to identify the main insights current literature offers regarding initial coin offerings (ICOs) and the avenues for future research. Design/methodology/approach – The approach consists of a systematic literature review of 130 papers from the SCOPUS database published in English between January 2018 and December 2020,with supplemental semantic analysis of the abstracts to obtain key themes and concepts. Findings – Regulation and the determinants of ICO success are the main themes for current research and represent fruitful areas of continued scholarship. The research agenda in ICOs is just beginning and several topics and questions merit future inquiry: the behaviour of issuers and investors, the importance of human capital, the role of intermediaries and infomediaries and the use of signalling. Originality/value – To the knowledge, this is one of the first systematic studies of current literature in ICOs. It provides a roadmap for future work on a phenomenon that will only grow in significance.